Charmfall : a novel of the Dark elite - Neill, Chloe (Indigo, 2012)
Lily Parker, a junior at St. Sophia's School for Girls, is distracted by preparations for the fall formal when a Reaper infiltrates the school and Lily discovers that a magic blackout in Chicago may prevent her from driving him out.